SUATU TINJAUAN TERHADAP PENERAPAN DISSENTING OPINION DALAM PENYELESAIAN PERKARA KEPAILITAN - ABDUL RIFAI (JURNAL CIVIL LAW USU, 2013)
Abstrak : Inspection system at the level of the Court, including the Commercial Court to condition the three judges who examine a bankruptcy case. Changes in the condition of Indonesian justice especially by issuing Law No.. 35 of 1999 on the Amendment of the Act No.. 14 Year 1970 on Basic Provisions of the Judicial Authority contributes dissent judges who examine cases including the case of a bankruptcy in the case verdict. Differences of opinion in deciding a case is called by the term "dissenting opinion". In this study the proposed formulation of the problem arises why the dissenting opinion in the case of bankruptcy and whether the conditions required in a bankruptcy court ruling that there is a dissenting opinion. Having done the research and data collection, it is known that the onset of a dissenting opinion in the case of bankruptcy in general is due to the independence of judges in deciding cases is limited by statutory provisions. While in particular the emergence of dissenting opinion in the case of bankruptcy is due to different backgrounds of judges who examined the bankruptcy case that is the career of judges and judges ad-hoc.Syarat-requisites required in a bankruptcy court ruling that there was a dissenting opinion dissenting opinion ruling the made in the form of an attachment that contains a statement of the judge expressly Member / chairman who made the dissenting opinion, that the decision is legally binding. The attachment is an integral part of the decision text. Justices dissenting opinion must still make the decision to sign and remain bound to the sound of the ruling dictum. In this study also suggested Chief executive decision makers especially in the law-making about arrangements regarding the emergence of dissenting opinions, especially in the case of bankruptcy should be a perfect set of conditions that must be met by the trial judge if there is a dissenting opinion.   Keywords: Dissenting Opinion, case, Bankruptcy